ANALYSIS OF MARKETING STRATEGY TO LEVERAGE THE BUSINESS GROWTH OF WASTE BANK TRI ALAM LESTARI - Didip Diandra (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
This research analyzes the marketing strategy of Waste Bank Tri Alam Lestari (TAL) to leverage their business growth. To optimize their performance, the effect of implementing customer-driven strategies and marketing mix is analyzed. The objectives of this study are to reveal the current marketing strategies implemented by Waste Bank TAL and to recommend the advance marketing strategy to optimize their business growth. This research used a qualitative research approach and the explanatory method by interviewing the owner and its stakeholders as primary data and other sources such as journals, books, and reports are as secondary data. The result of the analysis shows that the targeted market is a niche market, customized products, and superior products. Hence, there are some factors of the marketing mix that should be optimized through their brand awareness “Kreasi Menik” to leverage the business growth of Waste Bank TAL.